Estudo do extrato de Ginkgo biloba na prevenção de malformações em recémnascidos de ratas diabéticas - Sinzato, S. [UNESP]; Almeida, F. G. [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (My University, 2003)
The pregnant women presenting Diabetes mellitus develop metabolic alterations, that may cause damage to the fetal well-being and provoke anomalies and/or malformations. The antioxidant treatment has improved the embryonic development from streptozotocin diabetic rats. Several studies have shown that a Gingko biloba extract presents antioxidant effects and, in the present study, one of the G. biloba extract formulations was used (EGb761) - Tebonin (200 mg/Kg/day), given to the diabetic pregnant female rats. The aim was to evaluate the effect of the EGb761 treatment on the of anomalies and/ or malformations incidence of the offspring. Diabetes was induced in female rats using streptozotocin in a dose of 40 mg/kg. The rats were mated, and the pregnant animals were divided in two groups: Control (water) and experimental (G. biloba). At day 21 of pregnancy, the rats were killed, and their fetuses were analyzed and processed for anomalies and/or malformations incidence. The results demonstrated that control and experimental groups presented no external anomalies and malformations; increased incidence of skeletal anomalies and of visceral malformations, and lower rate of visceral anomalies and skeletal malformations. These data confirm no statistical difference and, therefore, EGb761 treatment did not cause changes. Thus, a dose of 200 mg/Kg/day of a Gingko biloba extract given during the pregnancy rat was ineffective in the prevention of the anomalies and/or malformations related to the diabetes.
Study of Gingko biloba extract to prevent the offspring malformations of diabetic female rats
Keywords: Diabetes; Gingko biloba; Malformations; Pregnancy; Rat; Ginkgo biloba extract; plant extract; animal model; antioxidant activity; bone malformation; congenital malformation; controlled study; diabetes mellitus; fetus malformation; Ginkgo biloba; nonhuman; oxidative stress; pregnancy; rat; streptozocin diabetes; Animalia; Ginkgo (genus)